Hubungan Agility Dan Koordinasi Mata Kaki Terhadap Keterampilan Dribbling Permainan Futsal Pada Esktrakurikuler Futsal Di Sdn 59 Kota Bengkulu - Genriyadi Genriyadi; Deffri Anggara; Febra Ritanza (Educative Sportive, 2026)
This study aims to determine the relationship between agility and eye-foot coordination with dribbling skills in futsal among students participating in the futsal extracurricular program at SDN 59 Bengkulu City. Dribbling is one of the fundamental techniques in futsal that requires good physical and motor abilities, particularly agility and eye-foot coordination. This research employed a quantitative approach with a correlational design. The population consisted of all students participating in the futsal extracurricular activities at SDN 59 Bengkulu City, and the sample was selected using total sampling techniques. Data were collected through agility tests, eye-foot coordination tests, and futsal dribbling skill tests. The collected data were analyzed using descriptive statistics, normality tests, and correlation analysis to determine the relationship between the variables. The results indicated that agility has a significant relationship with futsal dribbling skills, eye-foot coordination also has a significant relationship with futsal dribbling skills, and simultaneously agility and eye-foot coordination contribute positively to improving dribbling performance. Students with better agility and eye-foot coordination tend to demonstrate higher dribbling proficiency. Therefore, coaches and physical education teachers are encouraged to incorporate agility and coordination training into futsal extracurricular programs to enhance students' dribbling skills and overall playing performance.